FIRST AND SECOND-ORDER OP TIMALITY CONDITIONS USING APPROXIMATIONS FOR VECTOR EQUILIBRIUM PROBLEMS WITH CONSTRAINTS - Phan Quốc Khánh; Lê Thanh Tùng (Tạp chí Khoa học Đại học Đà Lạt)
We consider various kinds of solutions to nonsmooth vector equilibrium problems with functional constraints. By using first and second-order approximations as generalise derivatives we establish both necessary and sufficient optimality conditions. Our first-order conditions are shown to be applicable in many cases, where existing ones cannot be applied. The second-order conditions are new.